METHODOLOGICAL PRINCIPLES OF KNOWLEDGE OF THE EXTERNAL ENVIRONMENT OF THE FINANCIAL MECHANISM FUNCTIONING OF SOCIAL WELFARE: THE INSTITUTIONAL APPROACH (World of finance, 2023)
Introduction. The evolution of public ideas about the essence of social well-being, methods and tools for its provision, the emergence of unprecedented new threats to social development require an adequate response in the context of improving the architecture of the financial mechanism in accordance with the transformation of the external environment of its functioning. This necessitates the development of new scientific and methodological approaches to the scientific knowledge of the financial mechanism of public welfare as an open system interacting with the external environment, which will become a methodological basis for the development of this mechanism and optimization of its structure.The purpose of the article substantiate the methodological principles of the external environment of the functioning of the financial mechanism of public welfare through the prism of the institutional approach to scientific knowledge.Results. The article examines the external environment of the financial mechanism of public welfare as a set of institutions combined into four components and the factors generated by them that influence the development of this mechanism. The key features of such an environment are characterized and its components are defined, including political, economic, social, and ecological components. The leading institutions of each of the components of the external environment of the financial mechanism of public welfare are outlined.Conclusions. Identification of key features of the external environment, substantiating the cyclical relationship between its components and the basic institutions of the financial mechanism of public welfare made it possible to crystallize the priority directions of institutional changes, which should include: the development of institutions of public control, competition through the expansion of their influence on the sphere of public finance; the implementation of a comprehensive policy aimed at eliminating the causes of deformations in the development of social institutions and reducing the destructive impact of the factors generated by these deformations on the level of social well-being; formation of environmental institutions and strengthening of their influence on changing the configuration of the elements of the financial mechanism of public welfare.